PEMBELAJARAN FISIKA MENGGUNAKAN METODE EKSPERIMEN DAN DEMONSTRASI TERHADAP PRESTASI BELAJAR SISWA - Alpi Zaidah; Alpiana Hidayatulloh; Mulia Rasyidi (LPPM Institut Pendidikan Nusantara Global, 2021)
This study aims to determine the effectiveness of the use of the experimental method compared to the demonstration method on student achievement in the sub-topic of measuring instruments in MTs. Mu'allimin NW Kelayu for the academic year 2021/2022. This research is using experimental method. The study population was all MTs students. Mu'allimin NW Kelayu class VII for the academic year 2021/2022, a total of three classes. The research sample was determined randomly using cluster random sampling technique and two classes were taken. One experimental class with the experimental method, namely class VIIC and one control class using the demonstration method, namely class VIIB. Data collection techniques for learning achievement with the test method. The analysis prerequisite test used normality and homogeneity tests. For normality test using chi-squared and for homogeneity test using Bartlet method. The research hypothesis was tested using a one-party t-test, namely the right side with a 95% confidence level. Based on the results of the calculations for the analysis prerequisite test, namely the normality test, it can be concluded that the two samples came from a normally distributed population because χ2count < χ2table, namely for the experimental class 8.689 < 11.070 and for the control class 8.422 < 11.070. As for the homogeneity test, it can be concluded that the sample comes from a population that is not homogeneous because χ2count > χ2table, namely 5.881 > 3.841. From the results of the analysis on hypothesis testing, it was found that H0 was rejected and Ha was accepted because the price tcount > ttable was 1,926 > 1,707. Thus, it can be concluded that learning physics using the experimental method is more effective than the demonstration method on student achievement in the sub-subject of measuring instruments in class VII MTs. Mu'allimin NW Kelayu Academic Year 2021/2022.